Antimicrobial Perspectives of Active SiO2FexOy/ZnO Composites - Florin Matusoiu; Adina Negrea; Nicoleta Sorina Nemes; Catalin Ianasi; Mihaela Ciopec; Petru Negrea; Narcis Duteanu; Paula Ianasi; Daniel Duda-Seiman; Delia Muntean (Pharmaceutics, 2022)
The antibacterial activity of zinc oxide particles has received significant interest worldwide, especially through the implementation of technology to synthesize particles in the nanometer range. This study aimed to determine the antimicrobial efficacy of silica-based iron oxide matrix (SiO2FexOy) synthesized with various amounts of ZnO (SiO2FexOyZnO) against various pathogens. It is observed that, with the addition of ZnO to the system, the average size of the porosity of the material increases, showing increasingly effective antibacterial properties. Zinc-iron-silica oxide matrix composites were synthesized using the sol–gel method. The synthesized materials were investigated physicochemically to highlight their structural properties, through scanning electron microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX), and Fourier-transform infrared spectroscopy (FT-IR). At the same time, surface area, pore size and total pore volume were determined for materials synthesized using the Brunauer–Emmett–Teller (BET) method. Although the material with 0.0001 g ZnO (600 m2/g) has the highest specific surface area, the best antimicrobial activity was obtained for the material with 1.0 g ZnO, when the average pore volume is the largest (~8 nm) for a specific surface of 306 m2/g. This indicates that the main role in the antibacterial effect has reactive oxygen species (ROS) generated by the ZnO that are located in the pores of the composite materials. The point of zero charge (pHpZc) is a very important parameter for the characterization of materials that indicate the acid-base behaviour. The pHpZc value varies between 4.9 and 6.3 and is influenced by the amount of ZnO with which the iron-silica oxide matrix is doped. From the antimicrobial studies carried out, it was found that for S. aureus the total antibacterial effect was obtained at the amount of 1.0 g ZnO. For Gram-negative bacteria, a total antibacterial effect was observed in S. flexneri (for the material with 0.1 g ZnO), followed by E. coli (for 1.0 g ZnO). For P. aeruginosa, the maximum inhibition rate obtained for the material with 1.0 g ZnO was approximately 49%.